Digital transformation and its role in enhancing the security of accounting information An analytical study of the opinions of a sample of accountants from private banks in Baghdad Governorate: Transformasi digital dan perannya dalam meningkatkan keamanan informasi akuntansi Studi analitis mengenai pandangan sekelompok akuntan dari bank-bank swasta di Provinsi Baghdad - Lecturer.Dr. Jasim Mohammed Yaseen; Alaa Abd Al-hussen Omran Al-Zubaidi; Prof. Dr. Hikmat A. Alrawi (Academia Open, 2026)
General Background Digital transformation has become a strategic necessity for organizations seeking operational continuity and competitiveness in rapidly evolving technological environments. Specific Background In the banking sector, this transformation requires the integration of digital strategy, organizational culture, and leadership to ensure the protection of sensitive financial data. Knowledge Gap Despite growing adoption, limited empirical research connects these transformation dimensions with accounting information security, particularly in developing banking contexts. Aims This study examines the relationship between digital transformation dimensions and accounting information security in private banks in Baghdad. Results The findings reveal a statistically significant relationship and effect, with digital transformation explaining 46% of the variance in accounting information security and demonstrating a strong positive association. Novelty The study offers an integrated analytical model linking digital strategy, digital culture, and digital leadership with accounting information security within a specific regional banking context. Implications The results highlight the importance of strategic alignment, leadership development, and organizational culture in strengthening internal controls and safeguarding financial data in digital environments. KeywordsDigital Transformation, Accounting Information Security, Digital Strategy, Banking Sector, Organizational Culture Key Findings Highlights Strong statistical association identified between transformation practices and data protection Strategic alignment and cultural readiness linked to secure financial systems Leadership roles contribute to structured adoption of digital security practices